RANCANG BANGUN SMART HOME AUTOMATIC CONTROL dengan KOMUNIKASI MELALUI BLUETOOTH HC-05 BERBASIS MIKROKONTROLER ARDUINO dan ANDROID - Erwinnanto, Yohan; Kurniawan Nugroho, Andi; Heranurweni, Sri (eLEKTRIKA, 2017)
Design of Smart Home Automatic Control with Communications Via Bluetooth HC-05-Based Microcontroller Arduino and Android, will provide all the comfort, safety, security and energy savings, which takes place automatically and programmed via microcontroller, the house or building. Design of Smart Home Automatic with Control Communications Via Bluetooth HC-05-Based Microcontroller Arduino and Android is intended for automatic control processes. The system consists of seven sensors, keypad password for security doors, HC-05 Bluetooth GSM alarm application and device control applications aktuaktor, and aktuaktor buzzer, dc motors, lights, fans and fan dc exhausting. Among these sensors is a PIR sensor to detect theft, sensor MQ6 to detect leakage of LPG gas and smoke from fires, sensor HC-SR04 ultrasonic for automatic garage doors, fire sensors to detect a fire, the sensor LM35 to detect the temperature of the room, when the room temperature is hot the fan will be on automatically, when the cold room temperature will shut off the fan and LDR sensor to detect the intensity of light during the day which turn the lights off automatically and vice versa, thus saving energy. Homeowners can also control lights and monitoring sensors with android phones that are connected with communication via Bluetooth HC-05 microcontroller arduino, and can receive GSM alarm application sensors such as calling and sms. Test results are used UART communication data transmission between the microcontroller serial monitor monitor has an error of 0 % . HC - 05 Bluetooth can accept orders at the farthest distance of 11 meters . The fire sensor can work well when the fire was 110 cm . Sensor HC - SR04 is already working with an error rate of 0.3 %, so the accuracy of this tool by 100 % - 0.3 % = 99.7 % .Keywords : Security Door , Bluetooth HC - 05 , Microcontroller Arduino and Android , Application Control and Application GSM alarm.